Psychiatry for the person and its conceptual bases - Christodoulou, George (Int Psychiatry, 2008)
The 2005 General Assembly of the World Psychiatric Association (WPA) established the Institutional Program on Psychiatry for the Person (IPPP) in response both to a recognition of our profession’s historical aspirations and to recent international developments in clinical care and public health. These considerations point to the relevance of a comprehensive understanding of health and the centrality of the person in the delivery and the planning of healthcare. The IPPP’s goals can be summarised as the promotion of a psychiatry of the person (of the totality of the person’s health, both ill and positive), by the person (with clinicians extending themselves as full human beings), for the person (assisting the fulfilment of the person’s life project) and with the person (in respectful collaboration with the person who consults). Operationally, the IPPP has four components: conceptual bases, clinical diagnosis, clinical care, and public health. What follows is an initial review of the IPPP’s conceptual bases and an outline of its emerging activities.